Value of additional digital breast tomosynthesis for preoperative staging of breast cancer in dense breasts - Krammer, Julia; Stepniewski, Kathrin; Kaiser, Clemens G.; Brade, Joachim; Riffel, Philipp; Schönberg, Stefan; Wasser, Klaus (Anticancer research, 2017)
Aim: This retrospective study was initiated to determine the diagnostic value of additional preoperative breast tomosynthesis (DBT) for breast cancer staging in dense breasts. Patients and Methods: Sixty-six patients (69 breasts) with findings of American College of Radiology category 3 or 4 with Breast Imaging Reporting and Data System 5, 6 or 0 were included. All patients underwent digital mammography and additional DBT. Results: A total of 40/69 (58%) cancers were detected on both mammography and DBT, 23 (33.3%) were only seen on DBT (p=0.0001); 6/69 (8.7%) carcinomas were not detected by either method, of which three were invasive lobular carcinomas. Sensitivity for multifocal/multicentric disease was significantly higher on DBT (12/19, 63.2%) compared to mammography (4/19, 21.1%) (p=0.02), specificity was comparable (96.0% vs. 90.0%). Multifocal/multicentric disease was not detected on mammography nor DBT in 7/19 (36.8%) patients, including three invasive lobular carcinomas. Conclusion: DBT may significantly improve preoperative breast cancer staging in patients with dense breasts compared to conventional mammography alone. Nevertheless, limitations have to be expected in the case of invasive lobular carcinoma.
Gesehen am 20.08.2018